Brain Functional Connectivity in the Resting State and the Exercise State in Elite Tai Chi Chuan Athletes: An fNIRS Study - Wang, Shilong; Lu, Shengnan (Frontiers in Human Neuroscience, 2022)
This study aimed to reveal the characteristics of multi-circuit brain synergy between elite tai chi chuan athletes in resting and exercise states and to provide neuroimaging evidence of improvements in brain function by motor skill training. Functional near-infrared spectroscopy (fNIRS) was used to compare the brain activity of professional tai chi chuan athletes (expert group) and beginners (novice group) in resting and exercise states, and to assess functional connectivity (FC) between the prefrontal lobe and the sensorimotor zone. In the resting state, the FC between the left prefrontal lobe and the right sensorimotor area in the expert group was significantly lower than that in the novice group (P < 0.05). In the exercise state, the patterns of FC between the left prefrontal lobe and right sensorimotor area, the right prefrontal lobe and left sensorimotor area, and the left and right sensorimotor areas in expert group were significantly lower than that in novice group (P < 0.05). From the resting state to the locomotor state, the expert group experienced a greater absolute value of functional connection increment between the left prefrontal cortex and right sensorimotor area, and between the left sensorimotor area and right sensorimotor area (P < 0.05). This was positively correlated with the self-evaluation results of motor performance behavior. Under sports conditions, professional athletes' multi-circuit brain FC strength is significantly reduced, and their elite motor skill performance supports the neural efficiency hypothesis. This may be related to the high adaptation of the brain to specific tasks and the improvement of the integration of somatic perception processing and motor function.